2005
DOI: 10.1186/1471-2377-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Simpson-Angus Scale (SAS) in a naturalistic schizophrenia population

Abstract: Background: Simpson-Angus Scale (SAS) is an established instrument for neuroleptic-induced parkinsonism (NIP), but its statistical properties have been studied insufficiently. Some shortcomings concerning its content have been suggested as well. According to a recent report, the widely used SAS mean score cut-off value 0.3 of for NIP detection may be too low. Our aim was to evaluate SAS against DSM-IV diagnostic criteria for NIP and objective motor assessment (actometry).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 21 publications
3
66
0
1
Order By: Relevance
“…It further ignores subjective symptomatology. Recent work suggests that the Simpson-Angus is reliable but the traditional cut-off (0.3) is far too low, thus compromising specificity (Janno et al, 2005), a crucial point in interpretation. LOCF Analysis of data using 'last observation carried forward' (LOCF) is the standard statistical method to which data from all trials of new drugs was subjected but, it is suggested, this may have contributed advantage to new antipsychotics (Rosenheck, 2005).…”
Section: Other Issuesmentioning
confidence: 99%
“…It further ignores subjective symptomatology. Recent work suggests that the Simpson-Angus is reliable but the traditional cut-off (0.3) is far too low, thus compromising specificity (Janno et al, 2005), a crucial point in interpretation. LOCF Analysis of data using 'last observation carried forward' (LOCF) is the standard statistical method to which data from all trials of new drugs was subjected but, it is suggested, this may have contributed advantage to new antipsychotics (Rosenheck, 2005).…”
Section: Other Issuesmentioning
confidence: 99%
“…In the evaluation, the scores for all items are summed up and divided by 10. With a score of 0.3 and above, a diagnosis of neuroleptic-induced Parkinsonism is made (28).…”
Section: Simpson-angus Scale (Sas)mentioning
confidence: 99%
“…Antipsychotic side effect rating scales were first introduced in the 1970s. Since then a number of side effect and adverse effect scales have been developed [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…A number of scales focus primary on EPS such as the Abnormal Involuntary Movement Scale (AIMS) [28], extra pyramidal Symptom Rating Scale (ESRS) [25], the Simpson-Angus Scale (SAS) [24] and the Udvalg for Kliniske Undersogelser Side-Effect Rating Scale (UKUSERS) [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation